Structural Basis of the Substrate Specificity and Enzyme Catalysis of a Papaver somniferum Tyrosine Decarboxylase - Guan, Huai (Front Mol Biosci, 2017)
Tyrosine decarboxylase (TyDC), a type II pyridoxal 5′-phosphate decarboxylase, catalyzes the decarboxylation of tyrosine. Due to a generally high sequence identity to other aromatic amino acid decarboxylases (AAADs), primary sequence information is not enough to understand substrate specificities with structural information. In this study, we selected a typical TyDC from Papaver somniferum as a model to study the structural basis of AAAD substrate specificities. Analysis of the native P. somniferum TyDC crystal structure and subsequent molecular docking and dynamics simulation provide some structural bases that explain substrate specificity for tyrosine. The result confirmed the previous proposed mechanism for the enzyme selectivity of indolic and phenolic substrates. Additionally, this study yields the first crystal structure for a plant type II pyridoxal-5'-phosphate decarboxylase.